A new subgenus, Microidium, of Oidium (Erysiphaceae) on Phyllanthus spp. - To-anun C. (2014)
Powdery mildew fungi found on leaves, shoots, and stems of Phyllanthus acidus, P. amarus, and P. reticulatus proved to be a fungus having morphology unique in the Erysiphaceae. Light micrographs of a new germination pattern are added to discuss differences to other four germination patterns of the powdery mildews. The rDNA sequences (28S and 18S regions) of the fungi found on Phyllanthus spp. form a distinct monophyletic clade strongly supported by bootstrap (100%) in 18S + 28S trees, which indicates that the fungus is an isolated fungal group among the Erysiphaceae in tribal level. Because we cannot find the teleomorphic state of this fungus, a new subgenus Microidium of anamorphic genus Oidium is proposed to accommodate this organism. © The Mycological Society of Japan and Springer-Verlag Tokyo 2005.